Conversion of palm oil to new sulfur-based polymer by inverse vulcanization - Abbasi Amin; Nasef Mohamed Mahmoud; Yahya Wan Zaireen Nisa; Moniruzzaman Muhammad (E3S Web of Conferences, 2021)
The conversion of palm oil into a sulfur-based polymer by copolymerization with sulfur powder at its molten state is herein reported. The obtained sulfur-containing polymer was characterized using Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to demonstrate the successful conversion. The disappearance of the peaks related to vinylic groups of oil together with the appearance of a peak representing C-H rocking vibrations in the vicinity of C-S bonds confirmed the copolymerization of sulfur with oil. TGA revealed that the polymers have thermal stability up to 230°C under nitrogen and the polymers leave 10% sulfur-rich ash. DSC proved that a small amount of elemental sulfur remained unreacted in the polymer, which showed amorphous and heavily crosslinked structure resembling thermosets. These copolymers are an environmental-friendly polymeric material promoting the utilization of the abundant sulfur while also adding value to palm oil.